Student's Attitudes and Motivation Towards the Effectiveness of Open Distance Learning (ODL) in Malaysian Universities - Law, Kyra Ley Sy; Nesamalar Tharumaraj, Judith; Si, Josh Chong En (JOIV : International Journal on Informatics Visualization, 2025)
Online distance learning (ODL) has transformed the educational environment and ensured educational continuity during global crises. As ODL becomes a permanent mode of education, continuous research into its effectiveness is imperative. This study investigates the ARCS model as a mediator between student attitudes, learning platforms, and ODL effectiveness, focusing on student experiences and outcomes. Utilizing a quantitative approach, an online survey comprising 31 items across five domains, including the ARCS model, was administered to 123 participants currently or previously engaged in ODL. The findings reveal that ODL effectiveness is significantly enhanced by positive motivational factors supported by psychological and emotional attitudes. Contrary to initial assumptions, platform availability, and accessibility do not independently influence ODL effectiveness; instead, motivation positively mediates effectiveness. This study provides institutions with the flexibility to improve learning platforms and offers insights to boost student motivation. Additionally, the study underscores the importance of fostering supportive attitudes to maximize ODL benefits. Recommendations for future research include exploring other mediating factors that may impact ODL effectiveness and examining diverse student populations to generalize the findings further. By addressing these areas, educational institutions can better understand the dynamics of ODL and implement strategies to enhance student experiences and outcomes. This study contributes to the growing knowledge of ODL, highlighting critical areas for institutional improvement and student support. It emphasizes the need for a holistic approach to educational technology, where motivational and attitudinal factors are integral to achieving effective and impactful online learning.